A Suspected Allergic Reaction to Boal Fish (Wallago Attu) - Ramesh Puri; Jayati Batra (International Healthcare Research Journal, 2020)
Consumption of fish has increased around the globe due to its high nutritional value and this has led to an increase in incidence of allergic reactions to fish. Reactions to fish are not only mediated by the immune system causing allergies but are often caused by proteins, metals, various toxins and parasites. Allergic reactions to fish can range from being mild and self-limiting to serious and life threatening. We report a case of an adult with suspected allergic reaction to Boal fish (Wallago Attu) who developed contact dermatitis during marinating process. Application of steroids and administration of oral antihistaminic led to a quick recovery.